Role of Ayurveda in the Prevention and Management of Timir-A Conceptual Study. - Dansena, Gulshan; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2022)
Visual disturbances are described in Ayurveda under the terms Timira, Kacha, and Linganasha. Timira is an eye ailment that begins with Avyaktya Darshana and progresses to total vision loss. Timira has no independent etiological variables at the eye. Timira is characterized by Sushruta as Ghora Roga, which causes visual disturbances due to the accumulation of Doshas in various Patalas of the eye. Timira is a disorder of the Drusti Mandala that begins with impaired vision and progresses to full blindness if left untreated. The entire globe is looking at alternate medical systems to avoid surgical problems, as well as preventative ophthalmology to improve and retain eyesight. In this situation, having a thorough understanding of the Timira is critical for appropriate management of the illness. While considering the sign and symptoms it can be correlated with Cataract, Myopia, Keratoconus etc. regarding similarity with modern; different author has different opinions. A review of Timira from several sources has been compiled here, with a focus on cataract and myopia.